2015
DOI: 10.2147/dddt.s93912
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits human glioma cells via STAT3 degradation by the ubiquitin–proteasome pathway

Abstract: We investigated the underlying mechanism for the potent proapoptotic effect of paeoniflorin (PF) on human glioma cells in vitro, focusing on signal transducer and activator of transcription 3 (STAT3) signaling. Significant time- and dose-dependent apoptosis and inhibition of proliferation were observed in PF-treated U87 and U251 glioma cells. Expression of STAT3, its active form phosphorylated STAT3 (p-STAT3), and several downstream molecules, including HIAP, Bcl-2, cyclin D1, and Survivin, were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…As expected, we also found that Pae inhibited translocation of STAT3 to the nucleus in RT4 cells. It is noteworthy that a recent study conducted by Nie et al (13) found rapid down-regulation of STAT3 that was consistent with its accelerated degradation, and the pro-degradation effect of Pae on STAT3 was mainly through the ubiquitin-proteasome pathway. Therefore, these findings clearly indicate that deactivation of STAT3 by Pae contributes to its inhibitory effects on BCa development.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…As expected, we also found that Pae inhibited translocation of STAT3 to the nucleus in RT4 cells. It is noteworthy that a recent study conducted by Nie et al (13) found rapid down-regulation of STAT3 that was consistent with its accelerated degradation, and the pro-degradation effect of Pae on STAT3 was mainly through the ubiquitin-proteasome pathway. Therefore, these findings clearly indicate that deactivation of STAT3 by Pae contributes to its inhibitory effects on BCa development.…”
Section: Resultssupporting
confidence: 58%
“…Pae, extracted from RPA, is a natural anti-cancer medicine. Many pharmacological studies have reported that Pae exerts anti-cancer and anti-proliferative activity in cultured tumour cells, as well as in tumour xenograft models (12)(13)(14)(15). In 2016, Lin et al (16) reported the anti-proliferative properties of RPA extract on BCa, both in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pool of STAT3 in cells is submitted to a fine regulation consisting in several mechanisms. This includes a synthesis-degradation cycle, controlled by proteasomedependent pathways, that regulates total STAT3 availability [60,61]. Another mechanism is an activation-inactivation cycle that makes STAT3 activation transient as a rule.…”
Section: General Description Of Stat3 Pathway Signallingmentioning
confidence: 99%
“…Paeoniflorin (PAE) is a principal bioactive component of the root of Paeonia lactiflora Pall., a medicinal herb species found in Korea, Japan and China ( 10 ). In Traditional Chinese Medicine, PAE has been widely used ( 11 ). It has been reported that PAE exerts numerous pharmacological effects, such as anti-inflammatory ( 12 , 13 ), anti-allergy ( 14 , 15 ), immunoregulatory ( 16 , 17 ), neuroprotective ( 18 ) and hepatoprotective effects ( 19 ).…”
Section: Introductionmentioning
confidence: 99%